PENGARUH PERSEPSI KUALITAS DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan tahun 2016-2019 pengguna Smartphone Samsung) - Novia Eka Anggraini; N Rachma; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This research was aimed to test and analyze the effect of quality perception and brand image simultaneously to the purchase intention of Samsung smartphone,the effect of quality perception to the purchase intention of Samsung smartphone, and the effect of brand image to the purchase intention of Samsung smartphone. On this research, the total population of students of Economics and Business Faculty of UNISMA, generation of 2016-2019 who used Samsung smartphone was unknown, therefore, the sample of research exerted Malhotra theory as many as 75 respondents. Based on the data collection, the researcher analyzed the data through multiple linear regression test. This data analysis resulted these following information:1) The quality perception and brand image was simultaneously able to affect positively and significantly to the purchase intention of Samsung smartphone on students of Economics and Business Faculty of UNISMA, generation of 2016-2019, 2) The quality perception was able to affect positively and significantly to the purchase intention of Samsung smartphone on students of Economics and Business Faculty of UNISMA, generation of 2016-2019, 3) The brand image was able to affect positively and significantly to the purchase intention of Samsung smartphone on students of Economics and Business Faculty of UNISMA, generation of 2016-2019. Keywords: Quality Perception, Brand Image, Purchase Intention